2019
DOI: 10.1111/cob.12330
|View full text |Cite
|
Sign up to set email alerts
|

Relation between cognitive restraint and weight: Does a content validity problem lead to a wrong axis of care?

Abstract: Summary The aim of this research is to examine the relation between weight and cognitive restraint (CR), which is the intention to control food intake in order to maintain or lose weight, in a general French population sample. Is CR more prevalent in individuals with obesity than overweight, underweight or normal‐weight subjects in this cross‐sectional study? Are people affected by obesity non‐restrained eaters? A total of 507 French people (80.2% women and 19.8% men), aged 18‐78 years, responded to an online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…However, cognitive restraint was connected with higher BMI, which is consistent with some previous research [ 79 , 80 , 82 , 83 , 84 ]; opposite results were also reported [ 85 ]. Association between CR and obesity is complex.…”
Section: Discussionsupporting
confidence: 91%
“…However, cognitive restraint was connected with higher BMI, which is consistent with some previous research [ 79 , 80 , 82 , 83 , 84 ]; opposite results were also reported [ 85 ]. Association between CR and obesity is complex.…”
Section: Discussionsupporting
confidence: 91%
“…The observation of this type of competitive mediation 28 suggests that a decrease in this eating habit among people with a high CR score may partially counter (and thus decrease) the risk of obesity. In addition, people with obesity frequently intend to eat healthier food and/or to eat less but do not succeed in doing so 29 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, people with obesity frequently intend to eat healthier food and/or to eat less but do not succeed in doing so. 29 …”
Section: Discussionmentioning
confidence: 99%
“…CR is expressed in the understanding that it is necessary to eat less than desired and in a healthier way. However, in obese individuals, it is more difficult to put this into practice when compared to overweight or eutrophic individuals ( 36 - 37 ) .…”
Section: Discussionmentioning
confidence: 99%